DEVELOPING STUDENTS' RESEARCH ABILITY AS A PEDAGOGICAL PROBLEM - Matiash, Olha; Kryvosheia, Mykhailo (Physical and Mathematical Education, 2025)
Formulation of the problem. In today’s world of rapid changes and increasing volumes of information, research ability has become one of the key competencies. The effective integration of a research-based approach into educational practices requires the development of new tools and methods that foster this ability in students within the modern educational environment. There is a growing need for contemporary interpretations of the following questions: How can modern students be taught to identify problems and explore problematic situations? What techniques, methods, and tools are relevant to ensure the effective development of students' research abilities?Materials and methods. The study involves the analysis, systematization, and generalization of research findings reflected in the publications of domestic and international authors, as well as personal observations and experience in teaching students.Results. The concept of "students' research ability" has been explained. The challenges that teachers need to overcome to create the necessary conditions for developing students’ research abilities have been highlighted: fostering motivation for research and a need for inquiry-based activity; addressing students' insufficient critical thinking skills; overcoming the stereotypical perception of research as a difficult and tedious process; tackling psychological barriers faced by individual students; organizing effective collaboration in research groups; and equipping students with adequate writing skills. The primary challenge lies in the insufficient theoretical and practical preparedness of teachers to implement effective methodologies for developing students' research skills.  Conclusion. An essential condition for creating a conducive environment for developing students' research skills is the integration of research methods into the educational process. A systematic approach allows research-based learning to be viewed as a system that combines specific goals, objectives, content, methods, and forms, aiming to achieve significant learning outcomes for students.
Keywords: research ability; research skills; research activity; challenges in teachers’ methodological work